Rethinking rehabilitation: socio-ecology of tanks and water harvesting in Rajasthan. Prepared for the IWMI-TATA Water Policy Research Program Annual Partners' Meet, 2002 - Shah, Tushaar; Raju, K.V. (IWMI-TATA Water Policy Research Program, 2002)
In the arid and semi-arid Indian state of Rajasthan, tanks and ponds have been a mainstay of rural communities for centuries. This paper assesses a rehabilitation strategy proposed for 1200 large tanks. It argues that treating tanks only as flow irrigation systems is very likely to result in a flawed strategy. As the experience of NGOs work shows, Rajasthan?s tanks belong more to the watershed development domain than to the irrigation domain and a strategy that views tanks as multi-use socio-ecological constructs, and which recognizes varied stakeholder groups is more likely to enhance the social value of tanks.